Trend Analysis on Production, Import, and Export of Vegetable Sub-Sector in Nepal - Adhikari, B.; Pokharel, A. (Journal of the Institute of Agriculture and Animal Science, 2020)
Vegetable sub-sector is the third most prioritized sub-sector of agriculture in Nepal. This sub-sector is characterized by heavy fluctuation in production. Despite being an agricultural country, Nepal is facing a huge trade deficit in the agriculture sector. A trend analysis was carried out to explore the change in cultivation area, production, yield, import, and export of the vegetables over the 10 years from 2009/10 to 2018/19. Data were collected mostly from secondary sources including different governmental publications and governmental portals which were analyzed using Microsoft Excel. It was observed that, although vegetable cultivation and overall production had increased during the period, the productivity was growing at slower pace, and hence the national demand for vegetables was not fulfilled by domestic production. This enhanced the import of vegetable commodities and further broadened the import-export gap. The study showed that Nepalese vegetable farming was mostly of subsistence type with a need for commercialization to decrease import and enhance export.